A Guide to Performing Systematic Reviews of Health and Disease - Gurusamy, Kurinchi (UCL Press, 2025)
This practical guide to performing systematic reviews in a healthcare context provides a step-by-step approach for students and health professionals. Using free, opensource software to extract data and perform the necessary meta-analyses, this guide navigates the process of reviews, from study design and randomised controlled trials to interpreting results and reporting your findings.